SUITABILITY OF WORK ROLE AND ORGANIZATIONAL COMMITMENT ON WORK ENGAGEMENT IN DISTRICT GOVERNMENT EMPLOYEES IN THE PROVINCE OF BALI - I Made Satriawan; Putu Indah Rahmawati; Ni Made Ary Widiastini (IJEBD (International Journal of Entrepreneurship and Business Development), 2023)
Work engagement has a very positive impact on individuals and organizations, because work engagement is a positive attitude towards work and the organization where they work. The research design can be interpreted as a strategy to organize research steps in order to obtain valid data according to the variable characteristics and research objectives. This research is an ex-post facto research (measurement after the event), because the research data for both the independent variable and the dependent variable have occurred before this research was conducted. Path Analysis (Path Analysis) is used to determine the magnitude of the relationship and the direct and indirect influence of work role suitability (X1), organizational commitment (X2), on work engagement (X3). Because the data obtained from the questionnaire is ordinal data, while the data analysis used to prove the truth of the hypothesis suggests a minimum of interval data, the ordinal data needs to be scaled up to an interval scale through the "method of successive interval. There is a significant influence of work role suitability and organizational commitment together on work engagement. The first research hypothesis is that there is influence from the suitability of work roles and organizational commitment on work engagement in employees of the Regional Government of the Regency of Bali Province. based on the results of the path analysis test or Path Analysis in Table 4.8 the results obtained are the magnitude of the influence of work role suitability on work engagement showing the results Ryx1x2 = 0.926, with a p-value of 0.000 <0.05, which states that Ho is rejected which means there is an influence from role suitability work and organizational commitment to work engagement. There is an influence of work role suitability on work engagement. The second research hypothesis is that there is an influence of suitability of work roles on work engagement in employees of the Regional Government of the Regency of Bali Province. based on the results of the path analysis test or Path Analysis in Table 4.8, the result is that the magnitude of the influence of work role suitability on work engagement is 0.771 with a p-value of 0.000 <0.05. There is an Effect of Organizational Commitment on Work Engagement. The third research hypothesis is that there is an influence of organizational commitment on work engagement in employees of the Regional Government of the Regency of Bali Province. based on the results of the path analysis test or Path Analysis in Table 4.8 the result is the magnitude of the influence of organizational commitment on work engagement of 0.388 with a p-value of 0.000 <0.05. Appropriateness of work roles and Organizational Commitment have a significant positive effect on work engagement in the Regional Government Employees of the Regency of Bali Province. Appropriateness of work roles has a significant positive effect on work engagement for Regional Government Employees of the Regency of Bali Province. Organizational Commitment has a significant positive effect on work engagement in the Regional Government Employees of the Regency of Bali Province.